NKX2-5 variants screening in patients with atrial septal defect in Indonesia - Rozqie, Royhan (BioMed Central Ltd, 2022)
Background: NKX2-5 variant in atrial septal defect patients has been reported. However, it is not yet been described in the Southeast Asian population. Here, we screened the NKX2-5 variants in patients with atrial septal defect (ASD) in the Indonesian population. Method: We recruited 97 patients with ASD for genetic screening of the NKX2-5 variant using Sanger sequencing. Results: We identified three variants of NKX2-5: NM004387.4:c.63A>G at exon 1, NM004387.4:c.413G>A, and NM004387.4:c.561G>C at exon 2. The first variant is commonly found (85.6) and benign. The last two variants are heterozygous at the same locus. These variants are rare (3.1) and novel. Interestingly, these variants were discovered in familial atrial septal defects with a spectrum of arrhythmia and severe pulmonary hypertension. Conclusion: Our study is the first report of the NKX2-5 variant in ASD patients in the Southeast Asian population, including a novel heterozygous variant: NM004387.4:c.413G>A and NM004387.4:c.561G>C. These variants might contribute to familial ASD risk with arrhythmia and severe pulmonary hypertension. Functional studies are necessary to prove our findings. © 2022, The Author(s).